Neuroactive hormones and personal growth: associations in Chilean adolescents (ages 12–25) with ovulatory dysfunction - del Río, Juan Pablo; Tapia, Valeska; Soto, Hugo; Vigil, Pilar (Frontiers in Psychology, 2024)
Hormones produced by the hypothalamic-pituitary-adrenal-gonadal (HPAG) axis are crucial for modulating central nervous system (CNS) function and development throughout a person's life. Consequently, disruptions in HPAG function can also impact psychological development, which is particularly significant during adolescence—a period marked by psychological growth and the maturation of the HPAG axis. An early indicator of HPAG alterations is ovulatory dysfunction (OD), a common condition among adolescents. This study explored the associations between neuroactive hormones and personal growth in adolescents with OD. Female participants aged 12-25 years with OD were recruited, and assessments were conducted to profile their basic hormonal levels and various dimensions of individual development, including Self-Concept Clarity, Sense of Coherence, Self-Esteem, Perfectionism, Self-Control, and Mood States. The results showed that adolescents with OD (n=117) had lower self-concept clarity and self-esteem compared to reference data. A significant portion of the sample displayed elevated levels of tension (71.25%), confusion (62.5%), fatigue (58.22%), and depression (52.6%). Self-esteem scores were negatively correlated with DHEAS (r=-0.224; p=0.026) and glucose (r=-0.249; p=0.010). Higher levels of free testosterone were associated with increased depression scores (coef=0.2398; p=0.002), whereas higher estradiol levels were linked to lower aggressiveness scores (coef=-0.0648; p=0.001). These findings indicate that hormonal imbalances in adolescents with OD could affect personal growth, with further research needed to establish causal relationships between the variables considered.